ACTR-70. A MULTISITE CLINICAL TRIAL OF SPECTROSCOPIC MRI-GUIDED RADIATION DOSE ESCALATION IN GLIOBLASTOMA PATIENTS. (11th November 2019) - Mellon, Eric; Gurbani, Saumya; Ramesh, Karthik; Weinberg, Brent; Kleinberg, Lawrence; Schreibmann, Eduard; Barker, Peter; Maudsley, Andrew; Shim, Hyunsuk; Shu, Hui-Kuo
Abstract: The standard of care for glioblastoma is neurosurgical resection followed by radiation therapy (RT) and temozolomide (TMZ) chemotherapy. Although RT is effective for glioblastoma, attempts to improve survival using RT dose escalation above 60 Gy have been largely unsuccessful. This may be because prior attempts have been targeted to resection cavity or enhancing tumor, which may not accurately predict areas at highest recurrence risk. To overcome the limitations of standard T1 and T2-weighted MRI in predicting tumor recurrence, we have shown that supplementation with 3D high-resolution spectroscopic MRI (sMRI) identifies actively proliferating tumor beyond areas of T1-enhancement by measuring endogenous metabolites and their ratios. Previously, we demonstrated that the choline to N-acetylaspartate ratio (Cho/NAA) best correlates with tumor cellularity in surgically resected tissue (ρ=0.82, p< 0.001) and, most importantly, areas of sMRI metabolic abnormalities predate disease recurrence in those same areas (Cordova et al, Neuro-Oncology 2016). Therefore, we seek to identify whether sMRI can be used by radiation oncologists to choose the optimal regions to target for RT dose escalation. To assess its feasibility and safety, we developed a web-based imaging platform designed specifically to incorporate sMRI into the RT planning clinical workflow and are using it in a multisite sMRI-guided dose escalation trial (NCT03137888; Emory, Johns Hopkins, U. Miami). Recently, we have completed full enrollment including 30 patients treated with sMRI-guided dose escalated RT across three institutions. We have demonstrated successful integration of sMRI into the RT planning workflow, and we have delivered sMRI-guided dose escalated RT plans to glioblastoma patients without severe adverse events to date. Follow-up data will be analyzed for overall and progression-free survival. Based on the feasibility and safety of this technique in the current trial, we plan to assess the efficacy of sMRI-guided dose-escalated RT on patient outcomes in a NCTN clinical trial.